The Research Progress and Challenges of Peptide Drugs in the Treatment of Non-Small Cell Lung Cancer: From Mechanism to Clinical Practice - Xiao, Jing (International Journal of Public Health and Medical Research, 2024)
Non-small cell lung cancer (NSCLC) is the most common lung cancer subtype, with rising incidence and poor prognosis due to difficult early diagnosis. Peptide drugs, known for their high selectivity, low toxicity, and flexible structure, are emerging as promising NSCLC treatments. This review covers recent advances in peptide drugs, focusing on mechanisms for targeting pathways, modulating immunity, and overcoming resistance. Challenges such as stability, bioavailability, and delivery efficiency are discussed, alongside strategies like chemical modifications, nanocarriers, and computational design to improve efficacy. Future prospects include combining peptide drugs with current therapies and utilizing AI for precise NSCLC treatment.